New insights from seismic tomography on the complex geodynamic evolution of two adjacent domains: Gulf of Cadiz and Alboran Sea. Issue 4 (29th April 2013) - Monna, S.; Cimini, G. B.; Montuori, C.; Matias, L.; Geissler, W. H.; Favali, P.
Abstract : [1] In this study, we present a three‐dimensional P wave upper‐mantle tomography model of the southwest Iberian margin and Alboran Sea based on teleseismic arrival times recorded by Iberian and Moroccan land stations and by a seafloor network deployed for 1 year in the Gulf of Cadiz area during the European Commission Integrated observations from NEAR shore sourcES of Tsunamis: towards an early warning system (EC NEAREST) project. The three‐dimensional model was computed down to 600 km depth. The tomographic images exhibit significant velocity contrasts, as large as 3%, confirming the complex evolution of this plate boundary region. Prominent high‐velocity anomalies are found beneath Betics‐Alboran Sea, off‐shore southwest Portugal, and north Portugal, at sublithospheric depths. The transition zones between high‐ and low‐velocity anomalies in southwest and south Iberia are associated to the contact of oceanic and continental lithosphere. The fast structure below the Alboran Sea‐Granada area depicts an L‐shaped body steeply dipping from the uppermost mantle to the transition zone where it becomes less curved. This anomaly is consistent with the results of previous tomographic investigations and recent geophysical data such as stress distribution, GPS measurements of plate motion, and anisotropy patterns. In the Atlantic domain, under the Horseshoe Abyssal Plain, the main feature is a high‐velocity zone found at uppermost mantle depths. This feature appears laterally separated from the positive anomaly recovered in the Alboran domain by the interposition of low‐velocity zones which characterize the lithosphere beneath the southwest Iberian peninsula margin, suggesting that there is no continuity between the high‐velocity anomalies of the two domains west and east of the Gibraltar Strait. Key Points: Seismic velocity changes delineate ocean-continent plate boundaries Alboran slab geometry adds information on processes that have shaped it in time No continuity in velocity structure between Cadiz Gulf and Alboran domains